2015
DOI: 10.1053/j.ajkd.2014.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Incidence Among US Medicare ESRD Patients Receiving Hemodialysis, 1996-2009

Abstract: Background Patients with end-stage renal disease (ESRD) receiving dialysis have been reported to have increased risk of cancer. However, contemporary cancer burden estimates in this population are sparse and do not account for the high competing risk of death characteristic of dialysis patients. Study Design Retrospective cohort study. Setting & Participants US adult patients enrolled in Medicare's ESRD program who received in-center hemodialysis. Factors Demographic/clinical characteristics. Outcomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
138
1
13

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 171 publications
(159 citation statements)
references
References 46 publications
7
138
1
13
Order By: Relevance
“…Of these, 39 were excluded, as they comprised 3 duplicate studies, 2 studies not written in English, 1 review, 21 from which the SIR and 95% CI could not be calculated, 10 studies on hospital-based cohorts and 2 on irrelevant topics. Finally, 22 cohort studies contained in 18 studies were included in the present meta-analysis (8)(9)(10)(11)(12)(13)(14)(15)(16)(22)(23)(24)(25)(26)(27)(28)(29)(30). The main characteristics of the studies included are presented in Table I.…”
Section: Description Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these, 39 were excluded, as they comprised 3 duplicate studies, 2 studies not written in English, 1 review, 21 from which the SIR and 95% CI could not be calculated, 10 studies on hospital-based cohorts and 2 on irrelevant topics. Finally, 22 cohort studies contained in 18 studies were included in the present meta-analysis (8)(9)(10)(11)(12)(13)(14)(15)(16)(22)(23)(24)(25)(26)(27)(28)(29)(30). The main characteristics of the studies included are presented in Table I.…”
Section: Description Of Included Studiesmentioning
confidence: 99%
“…The main characteristics of the studies included are presented in Table I. The earliest study began in 1989 (22) and the latest ended in 2015 (11). All the studies were population-based.…”
Section: Description Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall incidence of malignancy in the dialysis population is already higher when compared to the general population [2]. Moreover, malignancy in the post-transplantation period is considered to be even higher when compared to the dialysis population particularly in the second and third decades post-transplant [3,4] (in this case, the patient presented 16 years after transplantation).…”
Section: Discussionmentioning
confidence: 99%
“…Cyclosporine (CyA) has been linked with increased risk of malignancy mostly in studies analysing its use in dermatological conditions [19,20]. On the other hand, Tacrolimus-based immunosuppression has been associated with a higher incidence of malignancy and shorter time interval between transplantation and tumour detection [2,21]. Fuchs et al found no difference in the oncogenic potential between Tacrolimus and Cyclosporine [22].…”
Section: Discussionmentioning
confidence: 99%